PARADIGMA BARD PENDIDlKAN SAINS - Wuryadi Wuryadi (LPMPP Universitas Negeri Yogyakarta, 2003)
Education in science has been developing rapidly in its variousdimensions and this canbe considered a new paradigm in scienceeducation. The dimensions considered highly significant intheirdevelopment are the instructional approach, orientation to diversityof learners' characteristics, expansion of the orientation to educational output, and interinstitutional and international collaboration.Science educationis no longer considered sterile in characterwith orientationonly to the interest of understanding science anddeveloping scientific thinking. Human and social values that can bedeveloped through science education have startedto be discoveredand studied.An inter- and multidisciplinary character of scienceeducation is becoming more dominant and it willbe the characterthat tends to develop further in the future.Science education canbe used as a medium to identify theperspectiveof the nation's development and as a basis fortechnological development and nation building. The responsibilityofscience education for national development is increasingly becomingbigger and the educationin science needs to be renewedcontinuouslyin order not to be left behind by the nation it self.